2002
DOI: 10.1038/sj.bjp.0704907
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the chemokine receptor, hCCR1 in a stable transfectant and differentiated HL‐60 cells: antagonism of hCCR1 activation by MIP‐1β

Abstract: 1 C-C chemokine receptor-1 (CCR1) has been implicated in mediating a variety of in¯ammatory conditions including multiple sclerosis and organ rejection. Although originally referred to as the MIP-1a/RANTES receptor, CCR1 is quite promiscuous and can be activated by numerous chemokines. 2 We used radioligand binding and [ 35 S]-GTPgS exchange assays in membranes from a cell line transfected to express CCR1 (Ba/F3-hCCR1) to characterize a panel of chemokines (HCC-1, MIP1a, MIP-1b, MIP-1d, MPIF-1, MCP-2, MCP-3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 56 publications
3
23
1
Order By: Relevance
“…We determined that MIP-1ˇhad an IC 50 value for CCR1/G § 14 /293 cells of approximately 60 nM (600 ng/ml; Fig. 6), and this is in good agreement with the value obtained by Chou et al [6]. In our IPformation assays the highest concentration of MIP-1ǔ sed was approximately 50 nM (500 ng/ml), which should result in the occupation of a high percentage of the receptors present in the system.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We determined that MIP-1ˇhad an IC 50 value for CCR1/G § 14 /293 cells of approximately 60 nM (600 ng/ml; Fig. 6), and this is in good agreement with the value obtained by Chou et al [6]. In our IPformation assays the highest concentration of MIP-1ǔ sed was approximately 50 nM (500 ng/ml), which should result in the occupation of a high percentage of the receptors present in the system.…”
Section: Discussionsupporting
confidence: 90%
“…[21] demonstrated that MIP-1ˇhad a greater affinity than MIP-1 § for human neutrophils, 1.1 nM versus 3.2 nM. However, Chou et al [6] determined that in murine IL-3-dependent pro-B cells, MIP-1 § (IC 50 =56 pM) had a higher affinity than MIP-1ˇ(IC 50 =33 nM). In addition, they determined that MIP-1ˇwas a full agonist with an EC 50 value for stimulation of GTP + S binding to cell membranes of 39 nM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCL23 (MPIF-1) . CCL5 $ CCL4 (Chou et al, 2002). Furthermore, CCL4 was found to antagonize responses to the other ligands, suggesting it could be an endogenous inhibitor of CCR1 activity.…”
Section: A Ccr1mentioning
confidence: 96%
“…One remarkable feature of these receptors is their apparent lack variety of selectivity in regards to ligand binding. For example, MIPlais one of eleven identified chemokines associated with CCR1 binding and activation (Chou et al, 2002). Likewise, while a receptor for MIP-la, CCR5 has received the majority of its publicity through the identification of its role as a co-receptor for HIV (Deng et al, 1997).…”
Section: Discussionmentioning
confidence: 99%